Textile Industry in Indonesia Amidst the Impact of the Covid-19 Coronavirus Pandemic - Andri Sutrisno (Kybernology : Journal of Government Studies, 2022)
This paper discusses the political economic situation during the economy in textile and textile products companies trying to diversify products by producing Personal Protective Equipment (PPE) and masks as a strategy to survive in the midst of the impact of the coronavirus (Covid-19) pandemic that hit almost all joints in Indonesia caused by the Covid19 pandemic. Using david ricardo's theory of comparative excellence, this paper tries to show that the textile industry switches the function of producing personal protective equipment or medical devices as well as economic disruptions due to the impact of coronavirus.